Aquaponic Technology to Support Food Self-Sufficiency for the Community in Tarumajaya Village, Bandung Regency - Dudi Darmawan; Mukhammad Ramdlan Kirom; Asep Suhendi; Jihan Fadhil Nabilah; Reza Widehan; Fadli Septian Anugrah (Journal of Innovation and Community Engagement, 2024)
The community of Tarumajaya Village resides in an agrarian area. Vegetable farming is the predominant commodity cultivated in the region, such as carrots, potatoes, cabbage, and onions. The community's income heavily relies on vegetable farming. However, the majority of the population there are only employed as daily laborers. Land ownership is limited to a small fraction of the population who can afford it. Therefore, the community greatly needs additional income to meet their living needs. The issue of land ownership remains unresolved to date. This community engagement activity was aimed to provide a solution for the community to have their own land for independent cultivation. In a previous program conducted through Telkom's CSR scheme, 28 aquaponic installations and one greenhouse equivalent to 14 portable aquaponic units were built in two different neighborhood units. However, the program needs to be continued through sustained mentoring to have an impact on the community. It is expected that after this activity, the community would be able to independently develop this aquaponic system so that food needs can be met and it can become an additional source of income for the communities in these two neighborhood units.